2010
DOI: 10.2341/10-066-l
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Conversion of Etch-and-Rinse and Self-etch Adhesives Light-cured Using QTH or LED

Abstract: Clinical RelevanceThe effect of QTH and LED curing lights on the degree of conversion of bonding agents is material dependent. SUMMARYIn the current study, the degree of conversion (DC) of bonding agents photoactivated using QTH or LED light-curing units (LCUs) was eval- Bond-CS3) were tested. For SBMP and CSE, the primer was not used. The irradiance and spectral emission of the LCUs were obtained with a radiometer and spectrometer. The materials were placed onto the ATR cell as thin films, the solvent was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 21 publications
3
35
0
7
Order By: Relevance
“…The addition of 5 and 10 wt% of Ta2O5 influenced the DC compared to control group (p<0.05). However, all groups showed values above 50%, which is in agreement with the DC of the commercial adhesives in the literature 35,36) . The addition of fillers in an adhesive resin may change the DC 37) , due to the decrease of light transmission in the filled resin matrix.…”
Section: Discussionsupporting
confidence: 91%
“…The addition of 5 and 10 wt% of Ta2O5 influenced the DC compared to control group (p<0.05). However, all groups showed values above 50%, which is in agreement with the DC of the commercial adhesives in the literature 35,36) . The addition of fillers in an adhesive resin may change the DC 37) , due to the decrease of light transmission in the filled resin matrix.…”
Section: Discussionsupporting
confidence: 91%
“…8,10 In some situations, this characteristic favors the improved DC of dental adhesives. 11 However, the influence of different irradiances on the DC of composite resins is questionable.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…The EDX data were consistent with the Raman results. Previous studies have indicated a close relationship between DCs and bonding strengths of adhesives to dental hard tissues (Kanehira et al, 2006;Faria-e-Silva et al, 2010). A high DC may also reduce permeability of the bonding assembly (Cadenaro et al, 2005) and increase interfacial durability and resistance to degradation (Navarra et al, 2009).…”
Section: Discussionmentioning
confidence: 94%